Comparison of symmetric dimethylarginine, plasma aldosterone concentration, renin activity and systolic blood pressure between diabetic and non-diabetic cats with hypersomatotropism - Rey Amunategui, J. P. (2023)
Acromegaly in humans is associated with multiple comorbidites, including kidney disease. Growth hormone (GH) and insulin-like growth factor 1 (IGF-1) excess may promote changes in plasma aldosterone concentration (PAC) and plasma renin activity (PRA) in acromegalic humans. The impact of hypersomatotropism (HST) in renal function in cats is unknown. The aim of this study was to evaluate symmetrical dimethylarginine (SDMA), PAC, PRA and systolic blood pressure (SBP) in cats with HST and to compare if there are differences between diabetic and non-diabetic cats with HST.